School-Scale Microbe Bioreactor Kit: Introducing Fermentation Technology To The Secondary Schools - Luqman Hakim Ahmad Firdaus; Assaiyidah Aisyah Faisal; Wan Abd Al Qadr Imad Wan Mokhtar; Sugenendran Supramani; Rahayu Ahmad (Universiti Sains Islam Malaysia, 2024)
E-Proceeding: Insan Junior Researcher International Conference (iJURECON) 2020 Date: 17-18 November 2020 Organized by: Kolej Genius Insan Virtual Conference Page : 200-205